Pengaruh Ideologi Maskulin Terhadap Konflik Peran Gender Pada Laki-Laki Suku Batak Karo - Karina Meriem Beru Brahmana (Universitas HKBP Nommensen, 2019)
The purpose of this study is to measure the influence of masculine ideology on gender role conflict experienced by Karo men. The sample of this research is Karo male with 296 people with age range between 17 - 73 years and the average age is around 41.9 years. The scales used are The Male Role Norm Scale from Thompson & Pleck (1986) and The Gender Role Conflict Scale from O'Neil et al (1986). Regression test results showed that R = 0.469 and R2 = 0.220. This shows that the influence of masculine ideology on gender role conflict is 22% while the rest is influenced by other variables. This research is considered very important because the amount of research on gender role conflict in men is still limited in Indonesia but have a lot of negative impacts. Moreover, in general the tribes in Indonesia are dominated by patrilineal culture.